2014
DOI: 10.5489/cuaj.1979
|View full text |Cite
|
Sign up to set email alerts
|

Association between visceral and subcutaneous adiposity and clinicopathological outcomes in non-metastatic clear cell renal cell carcinoma

Abstract: Introduction: Visceral adiposity has been inconsistently associated with clinicopathologic features and outcomes of clear cell renal cell carcinoma (ccRCC); however, most studies were conducted in non-Western populations. We evaluated the associations between visceral and subcutaneous adiposity and clinicopathological characteristics of non-metastatic ccRCC patients in a Western population. Methods: The medical records of 220 surgically treated ccRCC patients with documented preoperative body mass index (BMI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Five studies have examined the VAT content in patients with localized and/or advanced RCC [25]. Among these, three reported that low VAT contents are associated with poor prognosis in patients with RCC [25], and one study reported no association between VAT contents and overall mortality [26]. Park and colleagues reported that the lowest and the highest vs. the second quartiles of the VAT% are associated with a higher risk of recurrence [23].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies have examined the VAT content in patients with localized and/or advanced RCC [25]. Among these, three reported that low VAT contents are associated with poor prognosis in patients with RCC [25], and one study reported no association between VAT contents and overall mortality [26]. Park and colleagues reported that the lowest and the highest vs. the second quartiles of the VAT% are associated with a higher risk of recurrence [23].…”
Section: Discussionmentioning
confidence: 99%
“…5,24 Naturally, BMI was considered as one of the crucial factors to calculate patients' obesity and to predict their prognosis with cancer. 15,[25][26][27][28] However, growing evidence suggested that BMI was only a rough initial measurement and it ignored more information about body fat components on an individual level. 29 Compared with BMI, body fat composition (such as VFA, SFA, and TFA), as a quantitative method by CT image, has recently been focused on its contributions to the progression of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…12 Nevertheless, the clinical study reported by Mano et al showed that neither SFA nor VFA was associated with tumor stage, grade or OS in a non-metastatic clear cell RCC cohort from the United States. 28 Recently, the significant relationship between high VFA and the progression of clear cell RCC among patients from the Chinese south-eastern coast was shown in the study led by Huang et al 31 These conflicting results clearly indicate that further study about the issue is required. In the current study, we provided more evidence to reveal the prognostic value of body fat composition.…”
Section: Discussionmentioning
confidence: 99%
“…1, Table 1) [5,8,9,, including a total of 6608 patients. Eleven studies concerned perioperative outcomes (Table 2) [8,9,[16][17][18][19][20][21][22][23][24], four studies concerned treatment toxicity (Table 3) [5,[25][26][27], and 16 studies concerned recurrence, progression, and/or mortality (Table 4) [21,23,[27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Search Outcomementioning
confidence: 99%
“…All but four studies [16,25,26,31] were single center historical cohort studies. Nineteen studies included a consecutive series of patients while nine studies did not report this [27,28,30,[33][34][35]39] or included participants of a clinical trial [25,31]. Fourteen studies had more than 90% completeness of CT scans, while 14 studies did not report this [16,28,33] or had less than 90% completeness [5,9,18,21,26,27,30,32,[38][39][40].…”
Section: Quality Assessmentmentioning
confidence: 99%